2022
DOI: 10.3390/biom12020299
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 Alleviates Doxorubicin-Induced Cardiotoxicity through the AKT/mTOR Signaling Pathway

Abstract: Doxorubicin (DOX) is an effective chemotherapeutic agent that plays an unparalleled role in cancer treatment. However, its serious dose-dependent cardiotoxicity, which eventually contributes to irreversible heart failure, has greatly limited the widespread clinical application of DOX. A previous study has demonstrated that the ribonucleotide reductase M2 subunit (RRM2) exerts salutary effects on promoting proliferation and inhibiting apoptosis and autophagy. However, the specific function of RRM2 in DOX-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…7 A). In a concentration-dependent manner, DIDOX (inhibitor of RRM2) [ 36 ] restored the decreased viability of Erastin-treated C28/I2 cells ( P < 0.05, Fig. 7 A), implying the involvement of elevated RRM2 in ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…7 A). In a concentration-dependent manner, DIDOX (inhibitor of RRM2) [ 36 ] restored the decreased viability of Erastin-treated C28/I2 cells ( P < 0.05, Fig. 7 A), implying the involvement of elevated RRM2 in ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The AKT/mTOR signaling pathway plays a critical role in the development of multiple diseases and can regulate various mechanisms such as inflammation, oxidative stress, apoptosis, and autophagy ( Jiao et al, 2022 ; Zhang et al, 2022 ). At the same time, it has been reported that p-AKT and p-mTOR expressions were down-regulated in cardiomyocytes after treatment with LPS( Qi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous method, we extracted proteins from cells and heart tissues for Western blot experiments ( Jiao et al, 2022 ). In short, we use 7.5–12.5% SDS-PAGE gel for protein separation and transfer it to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that circ-RBM23 could sponge miR-139-5p to inhibit its function in hepatocytes during the PH. Xiong et al 29 indicated that RRM2 activates the AKT pathway in renal cell carcinoma, and Jiao et al 30 found that RRM2 may regulate doxorubicin-induced cardiotoxicity through the AKT/mTOR signaling pathway. Huang et al 25 reported that AFAP1-AS1 upregulates RRM2 expression by sponging miR-139-5p in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%